AKRONIM DALAM INDONESIA LAWAK KLUB (ILK) - Faizah, Hasnah Faizah AR.; Jalil, Abdul Jalil; ', Susdamita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Acronyms are one of the shortening in IndonesianÂ  This acronym is widely used in the ILK. The use of acronyms in a comedy show is interesting. This needs to be analyzed to determine the shape, formation, function, and meaning of acronyms used in the ILK. This research is a qualitative with descriptive method. The data analyzed in this study were taken from ten videos ILK. From the analysis, it was found 75 data. 75 These data are classified by shape, formation, function, and meaning. Form of the acronym in ILK consists of forms of words, phrases, clauses, and sentences. The dominant form is the form of words total 66 acronyms. The dominant formation is the perpetuation of the various letters and syllables are difficult to formulate total 65 acronyms. The dominant function is pragmatic function total57 acronyms. The dominant meaning is the meaning of total56 acronym pragmatic. Key word: Acronym, ILK, shape, formation, function, meaning